Prevention of Stunting Counselling for Pregnant Mother and Mother with Toddler - Mentari, Witri Dewi; Muhammad, Syarif (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
Stunting is one condition that indicates the height of a toddler is shorter than other toddlers. A large number of stunting cases in Indonesia has become health problems. The prevalence of stunting in Sumedang is 20% and it is still above the high level of WHO standard. At least, 28,1% of toddler in Sumedang is the prevalence of stunting in this district (Dinkes, 2018). In Jayamekar Village, Cibugel subdistrict, Sumedang district, it confirms that there are 42 stunting cases. The lack of knowledge about stunting is one of the reasons for this case occurs more often in this area. For that reason, the counselling is needed especially in Jayamekar Village, Cibugel subdistrict, Sumedang district. The purpose for this counselling is to educate stunting and the prevention of stunting to the citizen of Jayamekar, especially pregnant mother, mother with children and toddler. The counselling method for this research was lecture that was delivered about stunting and the prevention of stunting to the participants. The result for this research was to increase the knowledge and awareness about the child development hence it can prevent stunting and decrease the stunting case percentage in Indonesia especially in Jayamekar village, Cibugel district, Sumedang district.